Penghulu Institution Credibility and Leadership: Critical Challenges in Administrative Reform (Journal of Governance and Development (JGD), 2019)
The institution of Penghulu is the oldest and longest in the history of government administration in Malaysia. Since 50 century ago the credibility and leadership of Penghulu is maintain at higher respect of society and government structure. However the credibility of the institution getting weak due to rapid urbanization, lower entry level requirements and inadequate stafï¬ng diminish the power and inï¬‚uence of Penghulu. They are no longer seen as the authoritative ï¬gure for rural development, deliver their functions and existence have been questioned. Building upon this framework, this paper attempts to examine the challenges facing by institution of Penghulu in deliver duties in Kedah state administration. The study utilizes a qualitative method that involves personal interviews of 10 currents and former Penghulu as well as former state secretary in Kedah. The ï¬ndings of the interviews are classiï¬ed based on three major themes: entry level requirements, human resource development, and symbol of reference.